Mapping studies of the Peach latent mosaic viroid reveal novel structural features - DUBÉ, AUDREY (Blackwell Publishing Ltd, 2011)
Knowledge of the structure of a viroid is critically important to elucidate the roles played by the various RNA motifs in the steps of the viroid's life cycle. A new technique, RNA‐selective 2′‐hydroxyl acylation analysed by primer extension (SHAPE), has recently been shown to be fast, reliable and applicable to the study of various RNA molecules. Consequently, this method was used to probe sequence variants of Peach latent mosaic viroid (PLMVd). Initially, probing data from RNA strands of both polarities of the Siberian C variant confirmed the secondary structures previously determined using both conventional and fastidious approaches. Subsequently, analysis of an Alberta variant showed an identical structure for the strand of (−) polarity, but the (+) polarity strand exhibited two differences from the Siberian C variant: the P11–L11 stem–loop domain formed a cruciform structure, and nucleotides from loops L1 and L11 were involved in the formation of a pseudoknot. The existence of both of these motifs was confirmed by site‐directed mutagenesis. The subsequent probing of 12 natural sequence variants led to the elucidation of the criteria governing the formation of this novel pseudoknot. Importantly, this study revealed that the heterogeneity of a viroid is not limited to its nucleotide sequence, but may also occur at the structural level.